Role of intracellular calcium stores in hair-cell ribbon synapse - Castellano-Muñoz, Manuel; Ricci, Anthony J. (Frontiers in Cellular Neuroscience, 2014)
Intracellular calcium stores control many neuronal functions such as excitability, gene expression, synaptic plasticity, and synaptic release. Although the existence of calcium stores along with calcium-induced calcium release (CICR) has been demonstrated in conventional and ribbon synapses, functional significance and the cellular mechanisms underlying this role remains unclear. This review summarizes recent experimental evidence identifying contribution of CICR to synaptic transmission and synaptic plasticity in the CNS, retina and inner ear. In addition, the potential role of CICR in the recruitment of vesicles to releasable pools in hair-cell ribbon synapses will be specifically discussed.